OPTIMASI PORTOFOLIO MEGGUNAKAN METODE MEAN VARIANCE EFFICIENT PORTFOLIO (MVEP) PADA SAHAM LQ45 - Paiz Jalaludin; Royyan Amigo; Laelatul Maziyah Wildan Mufaridho; Ani Nuraini; Dewi Susanawati (POLITEKNIK LP3I JAKARTA, 2024)
When investing, an investor will strive to maximize the expected return of investment and minimize risk. In stock portfolio investments, investors need the right strategy to determine the proportion of each stock in such a way that the resulting portfolio is an optimum portfolio. This research applies the Mean Variance Efficient Portfolio (MVEP) method as a portfolio optimization method for stocks in the Mining sector, Technology and Communication sector, and Consumer Goods sector indexed by LQ45. The stocks used as simulation data are GOTO, EXCL, ANTM, ITMG, and INDF. This study aims to find the optimum portfolio from a combination of several stocks by applying the MVEP method and calculating its risk level. The research results indicate that an optimum portfolio will be formed if the proportion for each stock is 1.94% for GOTO, 25.17% for EXCL, 2.39% for ANTM, 43.19% for ITMG, and 27.31% for INDF. With those proportions, the expected portfolio return is 0.0074% and the risk is 8.69%. The result is expected to serve as a basis for decision-making for investors when investing.